TEACHING TOOLS WITH THE USE OF PROPRIETARY TECHNOLOGIES IN PSYCHOLOGY CLASSES - Dilbar Negmatovna Alimdjanova; Sardorbek Utayev Toshpulatovich (Journal Park Publishing, 2023)
Education is one of the most important ways of obtaining education, which is commonly understood as mastering the system of knowledge developed by mankind. Process the assimilation of knowledge in the psychological and pedagogical literature is considered as a complex activity of students to master the centuries-old experience of mankind, reflected in educational subjects (modules). The structure of the learning process is the activity of the teacher – teaching and the activity of students - teaching. So, teaching and learning constitute the essence of the learning process, and its content is determined by the curriculum and programs. Learning outcomes – the quality of knowledge, skills, competencies, the level of education and development of students.
Keywords: method, teaching methods, technology, pedagogical technology, teaching technology, psychological and pedagogical technology, algorithm of actions, structure and signs of technology.